2016
DOI: 10.1177/0017896915608205
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of metabolic syndrome in Chinese adults: Implications for health education

Abstract: Objective: The objective of this study was to assess knowledge of metabolic syndrome (MS) among Chinese adults and provide directions for designing healthcare promotion schemes for improving MS awareness in the community. Design: The study adopted a cross-sectional design and a convenience sampling method. Method: Chinese adults aged 18–65 years and living in the community completed a self-administered questionnaire, providing socio-demographic information and indicating their knowledge of MS using a validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 29 publications
4
13
2
Order By: Relevance
“…Only 12.5% to 29.0% of the participants had heard about MetS [13,14], and fewer participants (10.0%) understood the definition of MetS [12]. Only a few studies have investigated the knowledge specifically on MetS [15,16,17,18,19,20,21]. These studies used either a single item or self-developed questionnaires to assess the level of MetS knowledge among general population or healthcare providers [15,16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Only 12.5% to 29.0% of the participants had heard about MetS [13,14], and fewer participants (10.0%) understood the definition of MetS [12]. Only a few studies have investigated the knowledge specifically on MetS [15,16,17,18,19,20,21]. These studies used either a single item or self-developed questionnaires to assess the level of MetS knowledge among general population or healthcare providers [15,16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…This may reflect the limitations of observational research that women were more likely to enroll in a wellness program, so whether this instrument is reliable and valid in men requires more research. Unlike a previous study involving those with at least two CVD risk factors (Lo, Chair, & Lee, ), we included those who had one or more CVD risk factors. The low number of risk factors may indicate a low level of physical limitations, which may then lead to high self‐efficacy for exercise (Neupert, Lachman, & Whitbourne, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, when participants are aware of the diagnosis of dyslipidemia, they can pay attention to selflearning of relevant information. People with normal HDL-C levels knew more about MS, which indicates the positive impact of information on disease management (Lo et al, 2015;Zhao and Zhang, 2008). Compared to other studies on CVDs and risk factors, this population also demonstrated broad discrepancies in knowledge, as well as inconsistency between knowledge and attitudes.…”
Section: Discussionmentioning
confidence: 99%